Penerapan Metode Moving Average Dalam Penentuan Harga Pokok Penjualan Barang Berbasis Web - Fikri Hamidy; Ikbal Yasin (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
Cost of Goods Sold (COGS) is the cost incurred by the company to produce or acquire goods which are then sold to customers. The main components in COGS include raw material costs, direct labor costs, and factory overhead costs required to produce goods. One of the problems in determining the cost of goods sold is the difficulty in estimating production costs accurately, which can result in selling prices that are not in accordance with the expected profit margin. In addition, another problem in determining the cost of goods sold is the lack of accurate data or information about costs related to product production and distribution, thus making the pricing process less efficient and less precise. The application of the moving average method in determining the cost of goods sold (COGS) of web-based goods offers an efficient and integrated solution for companies in managing their production costs. Using a web-based application, users can easily access and utilize moving average analysis features to even out fluctuations in raw material or production prices in real-time. The test results using blackbox testing by 100% show that all test scenarios that have been designed have been successfully passed by the application without any failures or malfunctions. A 100% test result gives the development team additional confidence that the app is ready to launch and is widely used by users.